Evolusi Embrionik Manusia dalam al-Qurâan (Mutawatir, 2013)
This article attempts to reread passages of the Koran on human creation process; QS. al-Hajj [22]: 5, QS. HÃ»d [11]: 61, QS. al-Sajdah [32]: 7, QS. al-SaffÃ¢t [37]: 11, QS. al-RahmÃ¢n [55]: 14 and others. The verses are read in order in accordance with the process of the creation of man. The recitation of this time directed at scientific interpretation. Therefore, some of the views of modern science such as medical and others taken into consideration and presented back in it. These readings provide information about the stage of evolution in human creation, not Darwinâs theory of evolution, but the evolution of embryonic, is called Darwinian evolution that occurs in the womb, not in the real world. Based on this it can also be known that man is not the off spring of other animals-which can be said to be lower than beings. This is because human beings as âIâ or ânafsâ is not limited to a combination of physical and spiritual, but also has a sense or qalb